2022
DOI: 10.7759/cureus.30574
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parenting and the Parent-Child Relationship on a Child's Cognitive Development: A Literature Review

Abstract: Various studies have been done on subjects such as parenting, parent-child relationships, parenting style, effortful parenting, the concept of parenting, the cognitive development of children, and the cognition of parents. This research is mainly based on parenting practice, child development, and maturation. Children's cognitive development starts in the first year of life and then progresses gradually. Children require positive parenting in painful and different situations. Parenting gives a child the confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Third, the present study also found a mediating effect of peer interactions between parenting style and emotion management skills, where authoritative parenting style could improve children’s emotion management skills by influencing their peer interactions. This finding is consistent with national and international research that higher levels of peer interactions are associated with authoritative parenting ( Bornstein and Bornstein, 2007 ; Morris et al, 2021 ; Lanjekar et al, 2022 ), suggesting that peer interactions play an important mediating role in the way parenting styles influence children’s emotion management skills. Authoritative parenting styles contribute positively to children’s peer interactions in a study of the relationship between effortful control and character anger in Chinese children, and that higher peer interactions enhances children’s good social adjustment function and cultivates individual pro-sociality and a sense of collective responsibility ( Zhou et al, 2004 ).…”
Section: Discussionsupporting
confidence: 89%
“…Third, the present study also found a mediating effect of peer interactions between parenting style and emotion management skills, where authoritative parenting style could improve children’s emotion management skills by influencing their peer interactions. This finding is consistent with national and international research that higher levels of peer interactions are associated with authoritative parenting ( Bornstein and Bornstein, 2007 ; Morris et al, 2021 ; Lanjekar et al, 2022 ), suggesting that peer interactions play an important mediating role in the way parenting styles influence children’s emotion management skills. Authoritative parenting styles contribute positively to children’s peer interactions in a study of the relationship between effortful control and character anger in Chinese children, and that higher peer interactions enhances children’s good social adjustment function and cultivates individual pro-sociality and a sense of collective responsibility ( Zhou et al, 2004 ).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the age distribution, in the current study children aged 3- 6 years who represented nearly two-thirds of the study sample, were the most likely to be significantly diagnosed with any DD than the younger group (1–3 years). Children aged 3–6 years are subjected to many risk factors such as; familial violence, lack of stimulating environment [ 71 ], chronic malnutrition with decreased immunity [ 72 ], and increased vulnerability to diseases [ 73 , 74 ] due to defective weaning procedures or the unhealthy dietary behavior. Another explanation could be, developmental delay being more noticeable and overt in this age group as compared to younger children .…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have examined the effects of parental anhedonia on adolescent children, early childhood is also a critical period in which high parent-child relationship quality predicts positive child developmental outcomes in several domains (Elicker et l., 1992;Lanjekar et al, 2022). In this study, we focused on associations between anhedonia and daily emotional and parenting experiences among parents of young children.…”
Section: Anhedoniamentioning
confidence: 99%